Influenza A triggered status asthmaticus requiring emergency ECMO - Guarracino, F.; Stefani, M.; Maremmani, P.; Corini, M.; Pini, S.; Tascini, C.; Menichetti, F.; Ambrosino, N. (Monaldi Archives for Chest Disease, 2016)
We describe a case of acute respiratory failure due to severe pneumonia triggered by the influenza A virus, rapidly evolving into a refractory status asthmaticus requiring emergent ECMO assistance, in order to facilitate the clinical management of patients suffering from this rare but life-threatening condition. This case report demonstrates that infection with influenza A virus can present with severe pneumonia and status asthmaticus refractory to medical and ventilatory treatment. When medical treatment and mechanical ventilation fail, extracorporeal membrane oxygenation therapy should not be delayed as it will avoid injury resulting from inadequate mechanical ventilation and lung hyperinflation.